A Descriptive Study of the Students' Problems in English Reading Comprehension of X grade at SMAS AMKUR Sungai Pinyuh in the Academic year 2021/2022 - Aditya, Denuk Ayu; Antonia, Tia (Proceedings International Conference on Teaching and Education (ICoTE), 2024)
This study investigates the problem of student English reading in the Senior High School of SMAS AMKUR Sungai Pinyuh in terms of types of material, reading tasks, and cognitive level of reading tasks. The participant of this study consists of 23 students of grade X Social Studies. The researchers used descriptive qualitative research to develop the material in teaching reading, especially for English subjects. Not only for the texts, vocabulary, and the information but also to build students"™ critical thinking in reading comprehension. The book used as the instrument is Bahasa Inggris SMA/MA/SMK/MAK Kelas X Edisi Revisi 2017 published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud. The findings based on the teacher"™s observation from the students showed that some texts are too long and most of the time the readers do not suitable to the local contexts, the text used unfamiliar words to the students, and the books do not provide the list of vocabularies, used direct information to the answers of the questions after reading the text. Based on the research findings, the recommendation to improve students' reading comprehension is that the teacher needs to be more selective to know that the material is suitable for the students.